2020
DOI: 10.48550/arxiv.2010.03481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ELMo and BERT in semantic change detection for Russian

Abstract: We study the effectiveness of contextualized embeddings for the task of diachronic semantic change detection for Russian language data. Evaluation test sets consist of Russian nouns and adjectives annotated based on their occurrences in texts created in pre-Soviet, Soviet and post-Soviet time periods. ELMo and BERT architectures are compared on the task of ranking Russian words according to the degree of their semantic change over time. We use several methods for aggregation of contextualized embeddings from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Within contextual LMs, BERT and ELMo per-form similarly for Russian. Rodina et al 2020 show that neither BERT nor Elmo outperform each other when fine-tuned using historical text in Russian to detect semantic change. Moreover, results from the shared task on Unsupervised Lexical Semantic Change Detection in 5 languages hosted at SemEval 2020 show that systems performing well over one language may not perform as well for other languages.…”
Section: Time Periodmentioning
confidence: 87%
See 1 more Smart Citation
“…Within contextual LMs, BERT and ELMo per-form similarly for Russian. Rodina et al 2020 show that neither BERT nor Elmo outperform each other when fine-tuned using historical text in Russian to detect semantic change. Moreover, results from the shared task on Unsupervised Lexical Semantic Change Detection in 5 languages hosted at SemEval 2020 show that systems performing well over one language may not perform as well for other languages.…”
Section: Time Periodmentioning
confidence: 87%
“…While the success in identifying these shifts may be limited, (Rodina et al, 2020) find that DSC identified by contextual LMs can have a strong correlation with human judgment of change.…”
Section: Time Periodmentioning
confidence: 93%